ETNOPEDAGOGIK DALAM PERTANIAN MASYARAKAT ADAT DESA CIUSUL CITOREK - Agusta, Ratu Meri; Asti Hardianti; Rena Komalasari; Ujang Jamaludin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to describe the ethnopedagogical system in rice farming practices among the indigenous community of Desa Ciusul Citorek. Through observation, in-depth interviews, and document analysis, it was found that the indigenous people possess local knowledge about seed selection, planting, cultivation, harvesting, and storage of rice. This system has proven its sustainability in maintaining soil fertility and preserving the environment. However, the system also faces challenges from climate change and the influence of modernization. This study highlights the importance of preserving local knowledge as a foundation for building more sustainable agriculture.